Regulation of AQP4 in the Central Nervous System - Vandebroek, Arno; Yasui, Masato (International journal of molecular sciences, 2020)
Aquaporin-4 (AQP4) is the main water channel protein expressed in the central nervous system (CNS). AQP4 is densely expressed in astrocyte end-feet, and is an important factor in CNS water and potassium homeostasis. Changes in AQP4 activity and expression have been implicated in several CNS disorders, including (but not limited to) epilepsy, edema, stroke, and glioblastoma. For this reason, many studies have been done to understand the various ways in which AQP4 is regulated endogenously, and could be regulated pharmaceutically. In particular, four regulatory methods have been thoroughly studied; regulation of gene expression via microRNAs, regulation of AQP4 channel gating/trafficking via phosphorylation, regulation of water permeability using heavy metal ions, and regulation of water permeability using small molecule inhibitors. A major challenge when studying AQP4 regulation is inter-method variability. A compound or phosphorylation which shows an inhibitory effect in vitro may show no effect in a different in vitro method, or even show an increase in AQP4 expression in vivo. Although a large amount of variability exists between in vitro methods, some microRNAs, heavy metal ions, and two small molecule inhibitors, acetazolamide and TGN-020, have shown promise in the field of AQP4 regulation.